FAMILY’S LIFE EXPERIENCE IN TAKING CARE CHILDREN WITH HIV/AIDS IN CIMAHI CITY - Lina Safarina (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Indonesia has increase in cases of HIV/AIDS significantly. HIV/AIDS incidence in children is increase too. Children with HIV infection are vulnerable to physical and psychosocial problems are complex. This raises the issue of the family in caring for children with HIV/AIDS. The purpose of this study was to explore in depth the experiences of family life in the care of children with HIV/AIDS. Methods. The study used a qualitative approach was phenomenological. This research was conducted during the months of July-August 2012 in Cimahi. The study was conducted on families who have children with HIV/AIDS. Method of data collection study using in-depth interviews. Analysis of the data used to describe the lived experience of families in caring for children with HIV/AIDS with Colaizi data analysis. Results. Children with HIV/AIDS had experience a variety of problems related to the infection opportunity, growth and development disability, education, social skills and acceptance in society. Discussion. Nurse can give information about caring children with HIV/AIDS, give the support to family to get VCT program, ARV supervision, motivation enhancement, child health, children need to learn and play, support family to join with PMTCT program to increase quality of life of the children and family. Keywords: Children with HIV/AIDS, Family’s Experience, Quality of Life